Histone deacetylases (HDAC) in physiological and pathological bone remodelling - Cantley, M.D.; Zannettino, A.C.W.; Bartold, P.M.; Fairlie, D.P.; Haynes, D.R. (Bone (New York, N.Y.), 2017)
Histone deacetylases (HDACs)22Histone deacetylases (HDACs). play important roles in the epigenetic regulation of gene expression in cells and are emerging therapeutic targets for treating a wide range of diseases. HDAC inhibitors (HDACi)33HDAC inhibitors (HDACi). that act on multiple HDAC enzymes have been used clinically to treat a number of solid and hematological malignancies. HDACi are also currently being studied for their efficacy in non-malignant diseases, including pathologic bone loss, but this has necessitated a better understanding of the roles of individual HDAC enzymes, particularly the eleven zinc-containing isozymes. Selective isozyme-specific inhibitors currently being developed against class I HDACs (1, 2, 3 and 8) and class II HDACs (4, 5, 6, 7, 9 and 10) will be valuable tools for elucidating the roles played by individual HDACs in different physiological and pathological settings. Isozyme-specific HDACi promise to have greater efficacy and reduced side effects, as required for treating chronic disease over extended periods of time. This article reviews the current understanding of roles for individual HDAC isozymes and effects of HDACi on bone cells, (osteoblasts, osteoclasts and osteocytes), in relation to bone remodelling in conditions characterised by pathological bone loss, including periodontitis, rheumatoid arthritis and myeloma bone disease. •HDACi can regulate bone remodelling by suppressing osteoclasts and promoting osteoblasts•HDAC isozymes have differing roles in differentiation and function of bone cells, osteoclasts, osteoblasts and osteocytes.•Novel isozyme-specific HDACi are critical to elucidate HDAC roles in bone remodelling and communication between bone cells.•For non-malignancies, such inflammatory arthritis, HDACi can be more beneficial in vivo at much lower doses.